CRYPTOCURRENCY AS AN INSTRUMENT FOR MITIGATING DEFAULT RISK IN CLO/CDO STRUCTURES (Вісник: Міжнародні відносини, 2025)
Background.Securitized financial products, in particular Collateralized Loan Obligations (CLO) and Collateralized Debt Obligations (CDO), are important tools for transforming credit portfolios into liquid market assets. Traditional approaches to credit risk management, including credit default swaps (CDS) and reserve accounts, have a number of limitations, such as counterparty dependence, high protection costs, and the immobilization of liquidity. The modern development of financial technologies, including blockchain, smart contracts, and stablecoins, opens up new opportunities for improving the efficiency and transparency of mechanisms for protection against default losses. This article proposes a model of an insurance crypto reserve integrated into the CLO/CDO structure, which eliminates counterparty risk, automates payouts, and increases capital efficiency through the use of DeFi protocols.Methods.In the process of preparing the study, a systems approach was applied to comprehensively examine the CLO/CDO architecture and the impact of the cryptocurrency reserve on the risk structure; a comparative method was used to assess the financial feasibility of the crypto reserve versus CDS; a structural-functional method was employed to analyze the waterfall mechanism and the role of tranching in risk distribution; analytical modeling and scenario analysis methods were used to calculate expected losses (PD, LGD), determine the optimal reserve size, and test the effectiveness of the model in various stress scenarios.Results.The study showed that implementing a crypto reserve based on stablecoins and smart contracts can fully offset expected credit losses within the CLO/CDO structure at a lower overall protection cost compared to CDS. The proposed model demonstrates the elimination of counterparty risk, instant payout activation upon predefined triggers, and the potential to generate additional income by allocating reserve assets to low-risk DeFi protocols. In a quantitative example, the crypto reserve covered losses of USD 600,000 while retaining a balance for subsequent events, and in a no-default scenario, provided the opportunity to accumulate an additional USD 70,000–100,000 over a five-year period.Conclusions.The proposed model of an insurance crypto reserve for CLO/CDO combines the advantages of blockchain technologies and traditional securitization principles, providing enhanced resilience, transparency, and flexibility in risk management. It can reduce protection costs, eliminate dependence on intermediaries, and improve capital efficiency. For the practical implementation of this concept, it is advisable to carry out pilot projects that take into account regulatory requirements, standardization of smart contracts, and testing the model under real market conditions. Further research should focus on comparing the effectiveness of the crypto reserve in different jurisdictions, assessing its interaction with other hedging tools, and developing mechanisms to protect against technological risks.
Keywords: cryptocurrency; monetary surrogates; default risk; bank asset securitization; CLO, CDO; credit default swap; financial friction; digital assets.